Feasibility Study for a Rapid Maritime Link for Passengers of the Lower-North-Shore - Conseils & Stratégies pour l'Avenir des Régions (PAR) (2013)
This study relates to the feasibility of a maritime link for passengers on the Lower North Shore aiming at meeting a need shown for accessibility of both citizens and tourist alike with an affordable, rapid link with improved frequency, between the different communities and lasting the summer period, departures from Natashquan and Blanc-Sablon.

Lower North Shore Youth Employability Forum - Fequet Griffin, Priscilla (Coasters Association, 2011)
The 2011 Lower North Shore Youth Employability Forum was coordinated to provide the youth on the Lower North Shore with a two day intensive training on employability skills and provide them a forum to discuss with our Council of Mayors and leading community organizations and institutions the labour force market on the Lower North Shore. The projected outcome of the forum was to expand youth’s awareness of the shortages in labour in certain skilled trades sectors of employment and to improve opportunities for youth living in smaller, rural communities where jobs and employment services are more difficult to find. Thus, the skills developed during the two day forum will allow youth to further develop their capacity to enter into the labour force and raise awareness around labour opportunities on the Lower North Shore.